Coupled effects of ageing and moisture on the fracture properties of Permeable Friction Courses (PFC). Issue 4 (21st March 2022) - Manrique-Sanchez, Laura; Caro, Silvia; Kim, Yong-Rak
ABSTRACT: The mechanical performance of asphalt mixtures with high air void content – like Permeable Friction Courses (PFC) – is significantly affected by climate-related processes. Previous studies have demonstrated that ravelling (i.e. the loss of aggregates from the surface of the PFC) is related to the quality of the stone-on-stone contacts within the microstructure of these mixtures. Since the material located at these contacts is asphalt mortar, the durability of the mixtures strongly depends on the mechanical properties of this phase. This paper evaluates, for the first time, the coupled effects of ageing and moisture on the mechanical and fracture properties of the asphalt mortar of a typical PFC. The climatic conditioning processes included short and long-term ageing and dry-wet-dry moisture vapour cycles. The linear viscoelastic and fracture properties of the PFC mortar specimens were characterised using Dynamic Mechanical Analyser (DMA) and Semi-Circular Bending (SCB) tests. The results showed that ageing impacted the dynamic modulus of the mortar, while moisture had a negligible effect on this property. Also, the coupled effects of long-term ageing and moisture cycles reduced the fracture energy and other fracture parameters of the mortar between 2 and 10 times with respect to the short-term ageing condition in dry state.